2020
DOI: 10.1186/s12935-020-01448-9
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG6 enhances the radioresistance and promotes the growth of cervical cancer cells by sponging miR-485-3p

Abstract: Background: Cervical cancer (CC) is the one of most common malignant gynecological tumors, which is characterized with the high mortality and recurrence rate. Previous studies have elucidated the oncogenic role of small nucleolar RNA host gene 6 (SNHG6) in some types of human cancers, whereas it is unclear whether it functions as an oncogene in CC. This study was aimed at unveiling the role of SNHG6 in CC. Methods: qRT-PCR analysis was implemented to evaluate the expression levels of SNHG6, miR-485-3p and STYX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…[9][10][11] Furthermore, accumulating evidence pointed out that SNHG6 was involved in drug resistance and radio-resistance. 12 SNHG6 was reported to promote the 5-fluorouracil resistance in colorectal cancer by regulating miR-26a-5p. 13 Also, SNHG6 sponges miR-485-3p to enhance radio-resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Furthermore, accumulating evidence pointed out that SNHG6 was involved in drug resistance and radio-resistance. 12 SNHG6 was reported to promote the 5-fluorouracil resistance in colorectal cancer by regulating miR-26a-5p. 13 Also, SNHG6 sponges miR-485-3p to enhance radio-resistance.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Also, SNHG6 sponges miR-485-3p to enhance radio-resistance. 12 Thus, it can be inferred that SNHG6 regulate 5-fluorouracil resistance and radio-resistance through mediating DNA damage response pathway, which is the main cause for cisplatin resistance as well. Besides, Cao et al reported that SNHG6 enhanced paclitaxel resistance as well, indicating its potential role in regulating the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG6 upregulation is associated with poor prognosis of patients with colorectal cancer [ 273 ]. SNHG6 can also enhance radio-resistance of cervical cancer cells [ 274 ]. In colorectal cancer cells, SNHG6 overexpression occurs due to SP1 stimulation and DNA copy number gains.…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…Importantly, lncRNAs can affects EMT via EZH2 regulation. The lncRNA H19 is a tumor-promoting factor capable of enhancing cancer proliferation and invasion via p53 down-regulation and subsequent induction of TNFAIP8 [ 274 ]. Silencing H19 is in favor of apoptosis induction and impairing breast cancer proliferation [ 296 ].…”
Section: Non-coding Rnas and Ezh2 Signalingmentioning
confidence: 99%
“…Importantly, the downregulation of miR-485-3p was found in glioblastoma patients, suggesting a promising prognostic target for glioblastoma (Wang, Zhang et al, 2017). Similarly, the cancer-inhibitory role of miR-485-3p was evidenced in breast cancer (Lou, Xiao et al, 2016), renal cancer (Lai, Xin et al, 2020), and cervical cancer (Liu, Liu et al, 2020). However, the association relationships between circ-KRT6C and miR-485-3p have not been fully elucidated yet in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%